2017
DOI: 10.1002/mnfr.201600963
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal high salt diet altered Adenosine‐mediated vasodilatation via PKA/BK channel pathway in offspring rats

Abstract: Prenatal HS diets altered Adenosine-mediated coronary artery vasodilatation in the offspring, which was linked to downregulation of cAMP/PKA/BK channel pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Prenatal malnutrition, similar to other risk factors, has been demonstrated to cause the development of various adult illnesses, including cardiovascular, metabolic, and nervous diseases . However, the mechanisms underlying this effect are still relatively unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prenatal malnutrition, similar to other risk factors, has been demonstrated to cause the development of various adult illnesses, including cardiovascular, metabolic, and nervous diseases . However, the mechanisms underlying this effect are still relatively unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal malnutrition, similar to other risk factors, has been demonstrated to cause the development of various adult illnesses, including cardiovascular, metabolic, and nervous diseases. [1][2][3][4][5][6][7] However, the mechanisms underlying this effect are still relatively unclear. In the present study, the maternal FBG level was significantly increased by high sucrose feeding during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously established a rat model of HSD (8% NaCl) during pregnancy and found that prenatal HSD affected their offspring's coronary artery contractility, glucose tolerance, and insulin sensitivity. [13][14][15] These recent studies aimed to identify defects in the system that the offspring exposed to maternal HSD during pregnancy. As part of this study, we sought to determine whether HSD impacts oocyte and embryo quality and examine the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%